Application of a novel lytic phage vB_EcoM_SQ17 for the biocontrol of Enterohemorrhagic Escherichia coli O157:H7 and Enterotoxigenic E. coli in food matrices - Zhou, Yan; Wan, Qiyang; Bao, Hongduo; Guo, Yonghao; Zhu, Shujiao; Zhang, Hui; Pang, Maoda; Wang, Ran (Frontiers in Microbiology, 2022)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 and Enterotoxigenic E. coli (ETEC) are important foodborne pathogens, causing serious food poisoning outbreaks worldwide. Bacteriophages, as novel antibacterial agents, have been increasingly exploited to control foodborne pathogens. In this study, a novel broad-host range lytic phage vB_EcoM_SQ17 (SQ17), was isolated, characterized, and evaluated for its potential to control bacterial counts in vitro and in three different food matrices (milk, raw beef, and fresh lettuce). Phage SQ17 was capable of infecting EHEC O157:H7, ETEC, and other E. coli strains. Morphology, one-step growth, and stability assay showed that phage SQ17 belongs to the Caudovirales order, Myoviridae family, and Mosigvirus genus. It has a short latent period of 10 min, a burst size of 71 PFU/infected cell, high stability between pH 4 to 12 as well as thermostability between 30°C and 60°C for 60 min. Genome sequencing analysis revealed that the genome of SQ17 does not contain any genes associated with antibiotic resistance, toxins, lysogeny, or virulence factors, indicating the potential safe application of phage SQ17 in the food industry. In Luria-Bertani (LB) medium, phage SQ17 significantly decreased the viable counts of EHEC O157:H7 by more than 2.40 log CFU/ml (p < 0.05) after 6 h of incubation at 37°C. Phage SQ17 showed great potential to be applied for biocontrol of EHEC O157:H7 in milk and raw beef. In fresh lettuce, treatment with SQ17 also resulted in significant reduction of viable cell counts of EHEC O157:H7 and ETEC at both 4°C and 25°C. Our results demonstrate that SQ17 is a good candidate for application as an EHEC O157:H7 and ETEC biocontrol agent in the processing stages of food production and food preservation.